Investigating the Nexus between Inspirational Leadership and Innovative Work Behavior among Public Sector Employees - Queiri, Abdelbaset; Awashreh, Raed; Rashdi, Mohammad Al; Sallem, Ramzi; Nejad, Hoda Alavi; AL-Maashani, Wafa Amur (Journal of Ecohumanism, 2025)
The purpose of this study is to investigate the impact of inspirational leadership on employees’ innovative work behavior in Omani public sector. Using a convenient sampling, data were collected from 175 employees occupying different Omani function in public sector. Measurement and path analysis in SEM was employed and the finding reveals that inspirational leadership that encompasses features such as self-efficacy, change orientation and empowerment are relevant in engaging employees with innovative work behavior. This research offers a validated framework that may enhance the creativity of the employees of the public sector from a leadership perspective. Interesting recommendations are given to engage in inspirational leadership development programs to be in service of the innovation and competitiveness that are the main pillars of the Omani vision 2020-2040 concretization.